2011
DOI: 10.1136/bjophthalmol-2011-300132
|View full text |Cite
|
Sign up to set email alerts
|

Long-term surgical outcomes of porous polyethylene orbital implants: a review of 314 cases

Abstract: PurposeThis study reports on the long-term surgical outcomes after the insertion of porous Medpor orbital implants into anophthalmic sockets.MethodsA retrospective chart review of 314 eyes from 314 patients who underwent evisceration, enucleation and secondary procedures using Medpor orbital implants was completed focusing on implant-associated complications and their corrective methods as surgical outcomes.ResultsThe mean follow-up was 50 months (range 6–107 months). The most common complication was blepharop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
59
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 23 publications
1
59
0
2
Order By: Relevance
“…8,9 However, it can also induce foreign body reactions leading to mucosal hypertrophy or scar contracture. 5,9,10 Ashenhurst et al 11 reported a case series of 8 patients with restrictive strabismus and diplopia following conventional Jones tube, which occurred from several months to as long as 6 years after insertion. Their cases resulted from conjunctival scarring at the Jones tube site causing EOM limitation.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 However, it can also induce foreign body reactions leading to mucosal hypertrophy or scar contracture. 5,9,10 Ashenhurst et al 11 reported a case series of 8 patients with restrictive strabismus and diplopia following conventional Jones tube, which occurred from several months to as long as 6 years after insertion. Their cases resulted from conjunctival scarring at the Jones tube site causing EOM limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Cosmetic appearance, motility, implant exposure and extrusion are the most frequently discussed complications between these two procedures. In a recent study by Jung et al ,1 the fornix contraction was noted in 13.9% cases of enucleation (with unwrapped porous polyethylene) versus 3% cases of evisceration (with porous polyethylene placed in scleral shell). We would like to discuss the risk and probable causes for fornix contraction after the enucleation/evisceration.…”
mentioning
confidence: 89%
“…In addition to the study by Jung et al ,1 another study Shoamanesh et al 2 noted three cases of fornix contraction in enucleation with porous polyethylene implant. Nakra et al 3 found fornix outcomes with poor patency scores for enucleation (20%–40%) with unwrapped implant as compared with evisceration (0%–10%) with implant placed in scleral shell.…”
mentioning
confidence: 90%
“…Previous studies provide no evidence that integrated implants are superior to non-integrated implants (2,24,25) . The superiority of porous polyethylene has been reported but others note that porous polyethylene has the same rate of complications as other porous (26) or non-porous implants (3) . Several case reports indicate that complications have occurred with all of the different types of implants.…”
Section: Anophthalmic Socket: Choice Of Orbital Implants For Reconstrmentioning
confidence: 99%